Mental health self-efficacy as a moderator between the relationship of emotional exhaustion and knowledge hiding: Evidence from music educational students - Zhou, Xuan (Frontiers in Psychology, 2022)
The knowledge and skills of employees could play a valuable role in organizational success. Organizations are seeking ways to create a knowledge-sharing culture to take full advantage of individual competencies. However, the knowledge-hiding behavior of individuals is a hurdle in the internal dissemination of knowledge and expertise. It becomes more critical in the case of teaching institutions, where the students are taught and trained. Scholars are now putting their efforts into seeking the antecedents and consequences of knowledge-hiding behavior. This study also attempts to determine the role of interpersonal distrust as an antecedent of knowledge hiding behavior of music education students. Based on the social exchange theory, the present study attempts to check the association of interpersonal distrust with emotional exhaustion and knowledge hiding. For empirical investigation, this study assumes that interpersonal distrust positively enhances knowledge hiding and emotional exhaustion, respectively. Moreover, the present study also attempts to check the association of emotional exhaustion with knowledge hiding. This study also assessed the mediating role of emotional exhaustion in the relationship between interpersonal distrust and knowledge hiding. This current study also aims to check the moderating role of mental health self-efficacy in the relationship between emotional exhaustion and knowledge hiding. For empirical investigation, the present study collected the data from 310 music learning students of various Chinese universities through a structured questionnaire method using a convenient sampling technique. This study applied partial least square structural equation modeling for empirical analyses using Smart PLS software. The findings of this study revealed that interpersonal distrust does not directly influence knowledge hiding; however, interpersonal distrust has a positive association with emotional exhaustion. The findings also acknowledged that emotional exhaustion positively correlates with knowledge hiding. The results also confirmed that emotional exhaustion positively mediates the relationship between interpersonal distrust and knowledge hiding. Further, the outcomes depicted that mental health self-efficacy negatively moderates the relationship between emotional exhaustion and knowledge hiding. In addition, this study's findings also serve the literature of knowledge hiding by providing important theoretical and practical implications.